Gulf of Mexico Hypoxia 2022: What's the Role of Plant Nutrition?. Issue 5 (5th August 2022) - Bruulsema, Tom
Abstract : Hypoxia in the Gulf of Mexico is an environmental issue connected to agricultural crop management in the Mississippi River watershed. Programs to improve nutrient stewardship in this watershed aim to improve nutrient use efficiency and reduce losses of nitrogen and phosphorus. Trends since the 1980s show increases in both crop production and the size of the hypoxic zone while the trends in nitrogen surplus have neither increased nor decreased. Provisional flow‐normalized river loads of nitrogen are decreasing. While improvements in adoption of 4R management of applied fertilizers and manures have been noted, opportunities for improvement also remain. While 4R practices will not solve the issue on their own, they can make an important contribution when integrated with soil conservation practices and changes to whole farming systems. Earn 1 CEU in Nutrient Management by reading this article and taking the quiz at https://web.sciencesocieties.org/Learning‐Center/Courses .